(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Arguments in legal interpretation. A critical survey ABSTRACT: the essay deals with some of the most common arguments of legal interpretation, i.e. the reasons given by interpreters in support of their attributions of meaning to normative provisions; in particular, the literal argument, textual arguments, the legislator’s intention, the teleological argument, the apagogical argument, the systematic arguments, the comparative argument and the judicial precedent view as an argument of interpretation will be addressed. SOMMARIO: 1. Premessa - 2. Argomento letterale - 3. Argomenti testuali - 4. L’intenzione del legislatore - 4.1. L’intenzione semantica - 4.2. L’argomento teleologico soggettivo - 4.3. L’argomento teleologico oggettivo - 5. Le cosiddette sviste del legislatore e l’argomento apagogico - 6. Argomenti sistematici - 7. L’argomento comparatistico e il precedente giudiziale.